Effect of pacing strategy modification on 200 m performance in athletics - Yoshimoto, Takaya; Chiba, Yoshihiro; Mizukubo, Soshi; Sato, Kentaro; Ohnuma, Hayato; Takai, Yohei (Frontiers in Sports and Active Living, 2025)
In the 200 m sprint, it remains unclear whether modifying pacing distribution can lead to improved performance. This study aimed to address this question through three approaches: (1) cross-sectional analysis of world-class sprinters, (2) longitudinal analysis of an elite Japanese sprinter, and (3) an intervention involving pacing strategy modification for that sprinter. The study comprised three components: (1) cross- sectional analysis of 53 official races by world-class sprinters, (2) longitudinal analysis of 8 official races by an elite Japanese sprinter, and (3) a pacing intervention based on these analyses. Pacing distribution was assessed using two indices: the percentage of each 10 m split time relative to the 200 m record (%ST), and the percentage of each 100 m split time relative to the 100 m personal record (%PR). Cross- sectional analysis showed that world-class sprinters tended to sprint relatively slow in the first half and faster in the second half of the 200 m. Longitudinal analysis indicated that the Japanese sprinter achieved faster overall times when his speed in the 100–200 m segment was higher. Based on these findings, the modified pacing strategy improved his 200 m record from 20.43 to 20.14 s. These findings suggest that a pacing strategy focusing on maintaining speed in the latter half of the race, by moderating early acceleration, may contribute to performance improvement in elite-level 200 m sprinting.